Disturbance Winners or Losers? Plants Bearing Extrafloral Nectaries in Brazilian Caatinga. (17th June 2015) - Leal, Laura C.; Andersen, Alan N.; Leal, Inara R.
Abstract Plants bearing extrafloral nectaries (EFNs) often have traits typical of pioneer species, and may be expected to proliferate in disturbed habitats. However, a negative effect of disturbance on visitation by attendant ants could prevent EFN‐bearing plants from acting as disturbance winners. Here, we address the effects of chronic anthropogenic disturbance on the abundance of EFN‐bearing plants and their interactions with attendant ants in Caatinga vegetation of northeastern Brazil. We recorded the abundance of EFN‐bearing plants, proportion of plants visited by ants and composition of ant attendant species at 24 sites varying in levels of disturbance. EFN‐bearing plants as a whole did not behave as a disturbance winner group. The responses of the 13 species to increasing disturbance were highly variable, with three species declining in abundance (loser species). The richness of ant species attending EFNs did not vary with disturbance, but species composition did. The overall proportion of EFN‐bearing plants attended by ants per 5‐min period was not affected by disturbance. However, for the three loser species, attendance decreased from about 50 percent with low and moderate disturbance to half that with very high disturbance. We hypothesize that disturbed sites are more stressful for loser species compared with other EFN‐bearing plants, with physiological stress resulting in lower production of EFN secretions and reduced attraction of ants. This would make such species double losers, with physiological stress at disturbed sites not only directly influencing their performance but also indirectly affecting it through the disruption of a key mutualism.